Creating Bonding with Children during a Pandemic Through Fun Cooking Activities - Nur Laela; Cut Citra Novita (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
Fun Cooking is an activity in which children make their own dishes with ingredients that have been prepared by their parents and this Fun Cooking activity is an activity that requires assistance from parents or teachers when in school. Fun Cooking is also an activity that trains eye and muscle coordination and can also train children's social emotional development, which is to create bonding between children and parents. The purpose of this study is to create bonding in early childhood. The method in this research is using descriptive qualitative method. The collection technique in this study used the observation technique, namely the researcher saw directly the fun cooking activities of the parents with the child, interviews, namely the researcher interviewed the child's parents, and documentation to obtain valid and strong data. The analysis technique used in this research is data reduction using the Miles and Huberman model and the validity of this study uses the triangulation technique. The results of this study show that Fun Cooking activities can create bonding between children and parents and can train children's social emotional development.